2004
DOI: 10.1016/j.neuron.2004.06.002
|View full text |Cite
|
Sign up to set email alerts
|

CBP Histone Acetyltransferase Activity Is a Critical Component of Memory Consolidation

Abstract: The stabilization of learned information into long-term memories requires new gene expression. CREB binding protein (CBP) is a coactivator of transcription that can be independently regulated in neurons. CBP functions both as a platform for recruiting other required components of the transcriptional machinery and as a histone acetyltransferase (HAT) that alters chromatin structure. To dissect the chromatin remodeling versus platform function of CBP or the developmental versus adult role of this gene, we genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
708
3
10

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 766 publications
(752 citation statements)
references
References 59 publications
31
708
3
10
Order By: Relevance
“…These models are reviewed in [198], and have been analyzed at the molecular level in different learning and memory tasks. Studies examining the effect of a partial or total loss of CBP function show the involvement of its HAT activity in LTP and LTM, and suggest that CBP is not required for the formation of short-term memory (STM) [47,[199][200][201][202]. Nevertheless, another study using a conditional model with complete CBP inactivation in excitatory neurons of the forebrain showed an impairment of both memory types [203].…”
Section: Transgenic Hat Animal Modelsmentioning
confidence: 99%
“…These models are reviewed in [198], and have been analyzed at the molecular level in different learning and memory tasks. Studies examining the effect of a partial or total loss of CBP function show the involvement of its HAT activity in LTP and LTM, and suggest that CBP is not required for the formation of short-term memory (STM) [47,[199][200][201][202]. Nevertheless, another study using a conditional model with complete CBP inactivation in excitatory neurons of the forebrain showed an impairment of both memory types [203].…”
Section: Transgenic Hat Animal Modelsmentioning
confidence: 99%
“…Several recent studies have demonstrated that chromatin modification, specifically histone hyperacetylation, plays an important role in the molecular mechanism of learning and formation of a long-term memory in Aplysia and mice [1,12,19,21]. Since associative learning is an integrated component of psychostimulant-induced sensitization [5,37], HDAC inhibitors may potentiate amphetamine-induced behavioral sensitization by enhancing associative learning and memory consolidation.…”
Section: Learning Processes Governing Amphetamine Sensitizationmentioning
confidence: 99%
“…Recent evidence indicates that regulation of chromatin structure also serves as an additional level of control in this cascade. In particular, memory formation has been shown to be associated with histone acetylation (Alarcon et al, 2004;Guan et al, 2002;Korzus et al, 2004;Levenson et al, 2004;Vecsey et al, 2007;Wood et al, 2005). This process of histone acetylation relaxes chromatin structure, making it more accessible to transcriptional machinery (Lunyak et al, 2002;Turner et al, 2002;Varga-Weisz and Becker, 1998).…”
mentioning
confidence: 99%